2019
DOI: 10.3390/su11184920
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Firm’s Capability and Dyadic Relationship of the Knowledge Base on Ambidextrous Innovation in Biopharmaceutical M&As

Abstract: In recent years, technological mergers and acquisitions (M&As) have become important strategic tools for enterprises to access and utilize new external knowledge. In particular, in the biopharmaceutical industry, M&A activities are actively being progressed due to an increase in new drug development costs, a decrease in R&D productivity, and the patent expiration of blockbuster drugs. However, there is a lack of research on the integrated view of (1) the acquirer’s capability and (2) the dyadic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…Furthermore, the effectiveness and efficiency of capturing, absorbing, and integration of knowledge during the M&A integration phase is facilitated through a learning mechanism which is generated through conducting many acquisition in the past (Hayward, 2002). In other words, prior experience can affect the flow of technological knowledge from the target to the acquiring firm (Jo et al, 2016;Lee et al, 2019).…”
Section: Manda Experience Randd Goal Orientation and Innovation Performmentioning
confidence: 99%
“…Furthermore, the effectiveness and efficiency of capturing, absorbing, and integration of knowledge during the M&A integration phase is facilitated through a learning mechanism which is generated through conducting many acquisition in the past (Hayward, 2002). In other words, prior experience can affect the flow of technological knowledge from the target to the acquiring firm (Jo et al, 2016;Lee et al, 2019).…”
Section: Manda Experience Randd Goal Orientation and Innovation Performmentioning
confidence: 99%
“…This research studied the influence of exploitation and exploration strategies on business performance to analyze firm strategy and the effect of the user role on business performance. To appropriately measure the effect, other variables, including firm strategy, age of the firm, R&D concentration, and market structure were considered [39][40][41][42]. Figure 1 shows the research framework.…”
Section: Research Framework and Hypothesismentioning
confidence: 99%
“…In order to investigate the effect of exploitation strategy on performance, we examined the factors of the strategy. First, the elements of exploitation strategy as examined in the literature are license sales, improved products or services, and marketing agreements [15,42,43]. The use of resources was analyzed in [44], including licensing and marketing agreements used to engage contracts and increase efficiency.…”
Section: Exploitation Strategy and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, in the context of inbound innovation, studies mainly focused on the concept of the absorptive capacity, as suggested by [7]. However, as firms began to have increasing interest in selling their technologies as a way of outbound innovation, the research on open innovation has moved from mainly considering the inbound process to investigating the outbound process and stressing the need for empirical studies on knowledge capacities [8,9].…”
Section: Introductionmentioning
confidence: 99%